A LEGAL-HISTORICAL REVIEW OF THE EU COMPETITION RULES. Issue 2 (24th April 2014) - Chiriţă, Anca D
Abstract This article aims to review EU competition rules by undertaking a historical purposive interpretation of the drafting process of the Treaty of Rome. It reveals new insights based on a consideration of several historical archives starting with the Schuman plan, the Founding Treaty establishing the European Coal and Steel Community and the negotiations of the Treaty of Rome. Questions of contemporary relevance are explored, relating to the goals of competition law, the historical distinction between 'object' and 'effect' under Article 101 TFEU, the possibility of an enforcement gap under Article 102 TFEU, the relationship between unfair competition and the prohibition of discrimination and, finally, the broader meaning of competitive distortions.